2016
DOI: 10.18632/oncotarget.9926
|View full text |Cite
|
Sign up to set email alerts
|

Important role of kallikrein 6 for the development of keratinocyte proliferative resistance to topical glucocorticoids

Abstract: One of the major adverse effects of topical glucocorticoids is cutaneous atrophy often followed by development of resistance to steroids (tachyphylaxis). Previously we showed that after two weeks, interfollicular mouse keratinocytes acquired resistance to anti-proliferative effects of glucocorticoid fluocinolone acetonide (FA). One of the top genes activated by FA during tachyphylaxis was Klk6 encoding kallikrein-related peptidase 6, known to enhance keratinocyte proliferation. KLK6 was also strongly induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…However, topical steroid has not been reported as a treatment of PPPK. Glucocorticoids can suppress the proliferation of keratinocytes by reducing mitotic rates and thereby have an antiproliferative activity . Chronic use of topical steroid results in epidermal thinning, especially thinning of the stratum corneum, together with atrophic changes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, topical steroid has not been reported as a treatment of PPPK. Glucocorticoids can suppress the proliferation of keratinocytes by reducing mitotic rates and thereby have an antiproliferative activity . Chronic use of topical steroid results in epidermal thinning, especially thinning of the stratum corneum, together with atrophic changes .…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids can suppress the proliferation of keratinocytes by reducing mitotic rates and thereby have an antiproliferative activity. 13 Chronic use of topical steroid results in epidermal thinning, especially thinning of the stratum corneum, together with atrophic changes. 14 We carefully speculate that this mechanism of glucocorticoid may have a therapeutic effect on PPPK which is induced by hyperproliferation of keratinocytes although further researches are needed to confirm this mechanism.…”
mentioning
confidence: 99%
“…KLK6 is induced by the phorbol ester PMA, a known inductor of MAPK, and is up-regulated in the skin of patients with several hyperproliferative/inflammatory diseases. Also, KLK6 is also induced upon chronic GC treatment likely as a mechanism aimed to regenerate the epidermis after GC-induced skin atrophy; in agreement with this, Klk6 KO mice showed decreased steroid tachyphylaxis [ 114 ].…”
Section: Gc Resistance Due To the Crosstalk Between Gr And Mapk Signallingmentioning
confidence: 78%
“…In mice, it was demonstrated that chronic exposure to GCs induced desensitization; instead of the initial rate of growth inhibition (around 10–15% of control level), keratinocyte proliferation returned to the basal levels and even increased after two weeks of treatment [ 113 ]. The activation of kallikrein (KLK)-related peptidase KLK6 may in part be responsible for the development of GC-desensitization [ 114 ]. KLK6 is induced by the phorbol ester PMA, a known inductor of MAPK, and is up-regulated in the skin of patients with several hyperproliferative/inflammatory diseases.…”
Section: Gc Resistance Due To the Crosstalk Between Gr And Mapk Signallingmentioning
confidence: 99%
“…(Meier, Dear et al, 1999). Επίσης βρέθηκε ότι η επιδερμίδα των Klk6 -/ποντικών είναι υποπολλαπλασιαστική όπως αναφέρθηκε και προηγουμένως (Kishibe, Baida et al, 2016) και παρουσιάζει κανονικά πρότυπα διαφοροποίησης (Zingkou et al, 2019).…”
Section: ποσοτική Pcr (Qpcr)unclassified